Le lussazioni traumatiche del ginocchio - Manca, M.; Isola, A.; D’Arcangelo, M.; Sirianni, R. (Lo Scalpello - Journal, 2018)
TRAUMATIC KNEE DISLOCATIONS Knee dislocations are rare and severe events. Their effects can be both acute, including extremely serious lesions of the vascular and nervous structures, and they may develop later, as a loss of function caused by damage to the ligamentous structures. The diagnosis can be insidious if joint lesions recover spontaneously before the patient reaches observation. Knowledge of the injury patterns and of the underlying traumatic mechanisms is therefore fundamental to prevent missed or incomplete diagnoses. To date, the debate remains open on the treatment, timing, technique and selection of materials for reconstruction, but also on the ideal diagnostic pathway for vascular lesions. In this article we analysed the different aspects of the problem, highlighting the emerging trends from the most recent literature on the subject.